Performance of Newly-Weaned Pigs Fed Alternative Sources of Protein - Naldo, Michaelito A.; Quilat, Jonathan; Garcia, Leonides D.; Frio, Arturo Jose L. (Silliman Journal, 2022)
Soybean meal combined with dried whey and plasma protein are the usual protein sources in diets for newly-weaned pigs. This experiment investigated whether yeast protein with added enzyme can replace plasma protein and dried whey in diets for newlyweaned pigs. A total of 630 newly-weaned piglets (6.8 kg mean BW) were randomly allotted to three dietary treatments in a twophase feeding program from 0 to 21 days from weaning (Phase1), and 22 to 49 days from weaning (Phase 2). Dietary treatments 1 (control diet) in both phases contained low levels of soybean meal (18%), and high levels of dried whey (15% in phase 1, 10% in phase 2), and plasma protein (5%). Dietary treatments 2 in both phases contained high levels of soybean meal (25%), moderate levels of dried whey (5% in phase 1, 2.5% in phase 2), no plasma protein, and moderate levels of yeast protein (3% in phase 1, 2% in phase 2). Lastly, dietary treatments 3 in both phases contained high levels of soybean meal (25%), no dried whey, no plasma protein, and high levels of yeast protein (4% in phase 1, 3% in phase 2). Treatments 2 and 3 were supplemented with a solid state fermentation (SSF) enzyme complex containing phytase, protease, amylase, cellulase, xylanase, and ß-glucanase as part of the alternative strategy being evaluated in this study. All experimental diets did not contain any antibiotics. Feed intake, total body weight gain, average daily gain (ADG, g/d), feed conversion ratio (FCR, feed/gain), and survival rate were recorded and computed for each phase, as well as for the whole duration of the trial. Fecal consistency was taken at days 7, 14 and 21, and recorded as fecal score. Percent of scouring piglets per pen at day 7 of the trial was also recorded and noted as scouring incidence. Intestinal samples were taken at day 7 and day 28 of the trial to measure duodenal villus height and crypt depth, and to calculate for villus-height-to-crypt-depth ratio (VCR). Feed intake, survival rate and fecal score at day 7 of pigs in treatment 3 during phase 1 were found significantly different (P <0.05), but no difference in the other growth and scouring parameters were observed during phase 2 and over-all duration of the trial. Only the crypt depth at day 7 of treatment 1 was different (P <0.05) among all intestinal morphology data taken. This study demonstrates that the combination of yeast protein and SSF enzyme complex can successfully replace plasma protein and whey powder as protein sources for newly-weaned pigs. This offers opportunities for cost savings when designing diets for newly-weaned pigs.